In Vitro Study of a Medical Device to Enhance Arteriovenous Fistula Eligibility and Maturation. Issue 4 (July 2015) - Loree, Howard M.; Agyapong, George; Favreau, Elyse G.; Ngai, Gwendolyn A.; Tansley, Geoff D.; Dixon, Bradley S.; Franano, F. Nicholas
Abstract : The arteriovenous fistula eligibility (AFE) system (Flow Forward Medical, Olathe, KS) is a small, temporary, wearable rotary blood pump system designed to rapidly dilate peripheral veins in hemodialysis patients and improve outcomes after arteriovenous fistula (AVF) creation. A benchtop pulsatile mock circulatory loop was developed to model forearm circulation and to compare the hemodynamics of the AFE system with those of a conventional radiocephalic AVF. The AFE system maintained a mean wall shear stress (mWSS) within the 2.5–7.5 Pa target range for cephalic outflow veins of 2–6 mm diameter, which when applied clinically will provide better control of mWSS during the outflow vein maturation process when compared with a conventional AVF. These results support further study to determine whether or not vein preconditioning with the AFE system under controlled levels of mWSS will promote improved AVF outcomes.